This is marketing : you can't be seen until you learn to see / Seth Godin - Godin, Seth
Over the past quarter century, Seth Godin has taught and inspired millions of entrepreneurs, marketers, leaders, and fans from all walks of life, via his blog, online courses, lectures, and bestselling books. He is the inventor of countless ideas and phrases that have made their way into mainstream business language, from Permission Marketing to Purple Cow to Tribes to the Dip. Now, for the first time, Godin offers the core of his marketing wisdom in one accessible package. At the heart of his approach is a big idea: great marketers don't use consumers to solve their company's problem; they use marketing to solve other people's problems. They don't just make noise; they make the world better.